ANALISIS SINERGITAS BRIGIF 4 MARINIR/BS DAN BALAI BESAR PERIKANAN BUDIDAYA LAUT DALAM MENINGKATKAN KESEJAHTERAAN PRAJURIT - Haris Tri Purnama; Danang Marsudi; Bambang Dilianto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
One of the tasks carried out by the 4th Marine Brigade/BS is marine cultivation in improving the welfare of soldier's families. The current condition of marine cultivation has been programmed and is running optimally, however, the collaboration between the Marine Cultivation Fisheries Center has not synergized well. So that the support given to Brigif 4 Marines/BS to improve the welfare of soldiers' families has not been optimal. Various family welfare problems that arise in Indonesian society, one of which is the decline in the economic level. The problem of family welfare is motivated by changes in people's lives in the era of globalization, which are accompanied by increasing living needs, increasingly fierce competition in life, inability and limitations to adapt. The purpose of this study is to see the effect of marine cultivation in improving the welfare of soldiers. This study uses a quantitative method which is a method for testing certain theories by examining the relationship between variables with research instruments based on statistical procedures. Data analysis This research used Statistical Product and Service Solutions (SPSS) software version 25, in determining the sample used the researcher used non-probability sampling with incidental sampling technique, to determine the number of samples using the Slovin formula so that the sample obtained was 70 respondents.